Improving Student’s Writing Skill through Four-Phase Technique on Accounting Students - Ni Made Ernila Junipisa; Ni Made Ayu Purnami (Jurnal Pendidikan Bahasa, 2022)
This research is aimed to find out whether or not the implementation of four-phase technique during students’ learning activities. A class of accounting class in Triatma Mulya University is participated as the participant of this research.  The required data were collected through the use of questionnaire, observation checklist, and writing test. The data from the questionnaire indicated that students had positive attitude toward the implementation of Four-Phase Technique. Four-Phase improves their motivation in learning English and this technique brings more fun to the process of learning. Moreover, it was found from observation data that the students were actively participated during Four-Phase implementation. Finally, the study proved that Four-Phase Technique improved students’ writing skill. Students’ mean score of writing  before implemented this technique was 57.20  in the beginning of the study the mean score  was 72,5 their mean scores improved from 78,94 to  84,23.